OsWRKY67 Plays a Positive Role in Basal and XA21-Mediated Resistance in Rice - Vo, Kieu T. X.; Kim, Chi-Yeol; Hoang, Trung V.; Lee, Sang-Kyu; Shirsekar, Gautam; Seo, Young-Su; Lee, Sang-Won; Wang, Guo-Liang; Jeon, Jong-Seong (Frontiers in Plant Science, 2018)
WRKY proteins play important roles in transcriptional reprogramming in plants in response to various stresses including pathogen attack. In this study, we functionally characterized a rice WRKY gene, OsWRKY67, whose expression is upregulated against pathogen challenges. Activation of OsWRKY67 by T-DNA tagging significantly improved the resistance against two rice pathogens, Magnaporthe oryzae and Xanthomonas oryzae pv. oryzae (Xoo). Reactive oxygen species (ROS) rapidly accumulated in OsWRKY67 activation mutant lines in response to elicitor treatment, compared with the controls. Overexpression of OsWRKY67 in rice confirmed enhanced disease resistance, but led to a restriction of plant growth in transgenic lines with high levels of OsWRK67 protein. OsWRKY67 RNAi lines significantly reduced resistance to M. oryzae and Xoo isolates tested, and abolished XA21-mediated resistance, implying the possibility of broad-spectrum resistance from OsWRKY67. Transcriptional activity and subcellular localization assays indicated that OsWRKY67 is present in the nucleus where it functions as a transcriptional activator. Quantitative PCR revealed that the pathogenesis-related genes, PR1a, PR1b, PR4, PR10a, and PR10b, are upregulated in OsWRKY67 overexpression lines. Therefore, these results suggest that OsWRKY67 positively regulates basal and XA21-mediated resistance, and is a promising candidate for genetic improvement of disease resistance in rice.